2018
DOI: 10.5935/1518-0557.20180006
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of ovarian follicular dominance during stimulation for IVM impacts usable blastocyst yield

Abstract: ObjectiveTo evaluate the influence of ovarian follicular dominance on the outcome of oocyte in-vitro maturation.MethodsThis retrospective cohort study included 21 patients with polycystic ovaries or polycystic ovary syndrome (Rotterdam criteria, 2004) subjected to 24 in-vitro maturation (IVM) cycles between October 2015 and January 2017. Patients undergoing IVM received minimal gonadotropin stimulation starting on day 2 or 3 of the cycle; ovum pick-up typically occurred on days 6 to 8. No hCG-trigger shot was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…Our findings showed a lower outcome efficiency compared with the non-hCG primed IVM cycles reported in the Walls et al study, which compared the outcome of 98 IVF cycles with 80 cycles of non-hCG primed IVM treatment in PCOS patients. They found that the cumulative clinical pregnancy and implantation rates were nearly 51% and live birth rate was 41.3% [14], which was consistent with other studies that used similar approaches [9,37]. These high rates of cumulative clinical pregnancy and implantation may be due to the transfer of blastocyst embryos in fresh and frozen ET cycles.…”
Section: Discussionsupporting
confidence: 79%
“…Our findings showed a lower outcome efficiency compared with the non-hCG primed IVM cycles reported in the Walls et al study, which compared the outcome of 98 IVF cycles with 80 cycles of non-hCG primed IVM treatment in PCOS patients. They found that the cumulative clinical pregnancy and implantation rates were nearly 51% and live birth rate was 41.3% [14], which was consistent with other studies that used similar approaches [9,37]. These high rates of cumulative clinical pregnancy and implantation may be due to the transfer of blastocyst embryos in fresh and frozen ET cycles.…”
Section: Discussionsupporting
confidence: 79%
“…Other sibling follicles undergo atresia. Whereas, for IVM cycles, most centers prefer to schedule oocyte retrieval when the diameter of DF reaches 10–12 mm or when the endometrial thickness reaches at least 5–6 mm for the PCOS patients without leading follicles [ 21 , 118 , 119 , 120 ]. DF size exceeding the upper limit can cause detrimental effects on the sibling immature oocytes, resulting in a decreased quality of the retrieved oocytes [ 21 ].…”
Section: Time Of Oocyte Retrievalmentioning
confidence: 99%